(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Alkaptonuria is a rare tyrosine metabolism disorder due to a deficiency of the enzyme Homogentisic Acid Oxidase (HGO) and it carries autosomal recessive inheritance. We report this case, for increasing awareness among the doctor’s society, so that early diagnosis of diseases from urine color. Case Presentation: A 14-month-old boy, 2nd issue of a consanguineous couple brought to Outpatient Department of Paediatric Nephrology with symptoms of staining of nappy following urination on 1st March 2022. His urine chromatography report shows a high concentration of homogentisic acid and later diagnosed with a case of alkaptonuria. Conclusion: Alkaptonuria has to be considered if any child presents with darkening of urine exposure to the atmosphere. Early identification of diseases would be beneficial for delaying potential complications. JCMCTA 2023 ; 34 (2) : 150-152